Influência do comprimento do pino de fibra de vidro na resistência à fratura de raízes fragilizadas - Junqueira, Rafael Binato [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aim in this study was to evaluate, in vitro, the influence of glass fiber posts of different lengths on the fracture resistance of roots submitted to different weakening protocols. Ninety bovine roots, of same dimensions, were endodontically treated and randomly distributed in 9 groups (n =10), according the weakening protocol (NW - non-weakened; MW - medium-weakened; HW - hard-weakened) and the post length (7 mm; 9 mm e 12 mm). The canals were prepared for the posts and, on the weakened roots, they were individualized with composite resin A chemically activated resin cement was used in all posts. After luting, coronary reconstruction was conducted with composite resin, based on standardized silicon matrix. To reproduce physiological mobility, root portion was covered by polyether and embedded in polyurethane. The thermomechanical cycling was realized under a load of 88 N at 1.200.000 cycles, with a frequency of 3.8 Hz. For the resistance of fracture analysis, the specimens were placed at 45 ° in a universal testing machine, with a load-cell of 100 Kgf, with speed of 1mm/min. After mechanical essay, the specimens were analyzed by stereomicroscope to classify the failure mode (reparable/irreparable). Numerical values (n = 10) obtained for specimens' fracture were subjected to statistical analysis ANOVA two-way and Tukey test (5% of significance). The frequencies of failure mode were compared by chi-square test. ANOVA showed that the association between length and weakening was statistically significant (p < 0.05). The post-hoc Tukey's test revealed that this difference was between NW and HW roots for posts of 12-mm in length. Chi-square test indicated association between failure mode and the length and weakening factors. It was concluded that highly-weakened roots with longer posts had lower fracture resistance values, as catastrophic mode was more predominant

O objetivo no presente estudo foi avaliar, in vitro, a influência do comprimento do pino de fibra de vidro na resistência à fratura de raízes submetidas a diferentes níveis de fragilização. Noventa incisivos bovinos, de dimensões semelhantes, tiveram as coroas removidas e foram instrumentados, obturados e divididos aleatoriamente em 9 grupos (n =10), de acordo com o protocolo de fragilização (SF - sem fragilização; FM - fragilização moderada; FS - fragilização severa) e o comprimento do pino utilizado (7 mm; 9 mm e 12 mm). Os canais foram preparados para o retentor e, nas raízes fragilizadas, os mesmos foram individualizados com resina composta. Foi utilizado um cimento resinoso quimicamente ativado para a cimentação de todos os pinos. Após a cimentação, foi feita reconstrução coronária com resina composta, com base em matrizes de silicone padronizadas. Para reprodução da mobilidade fisiológica, a porção radicular foi coberta com poliéter e incluída em poliuretano. A ciclagem termomecânica foi realizada sob cargas de 88 N em 1.200.000 ciclos, com frequência de 3,8 Hz. Para determinação da resistência à fratura, as amostras foram posicionadas a 45 ° em uma máquina de ensaios universal, com célula de carga de 100 Kgf e velocidade de 1 mm/min. Após o ensaio mecânico, os espécimes foram analisados em estereomicroscópio para classificação do tipo de fratura gerada (reparável/irreparável). Os valores de resistência obtidos foram submetidos a análise estatística ANOVA - dois fatores e teste de Tukey (nível de significância de 5%). As frequências dos tipos de fratura foram comparadas pelo teste qui-quadrado. Os resultados da ANOVA revelaram que a associação entre o comprimento do pino e a fragilização foi estatisticamente significante (p < 0,05). O teste de Tukey indicou que esta diferença foi entre as raízes não fragilizadas e com maior...
Keywords: Técnica para retentor intrarradicular; Fraturas dos dentes; Dentes - Raízes; Tooth Root